“You Know What I Mean?” The Pedagogical Canon of “Cannonball” Adderley - Jones, Ryan Patrick (Current Musicology, 2005)
"Those who can, do. Those who can't, teach." So reads a familiar adage often relayed to prospective teachers. Its appeal derives from a curious discon-nect-namely, that those who teach are compelled to do so by, or even in spite of, incapacity. Usually passed along by outsiders, this observation is rarely borne out by practical application in the educational field because the most effective teaching models lead directly by example, relying upon inspiration to make lasting impressions upon students.